Study of the Bc → Bsπ decay with the perturbative QCD approach - Sun, JunFeng; Yang, YueLing; Lu, GongRu (Science China. Physics, mechanics & astronomy, 2014)
The Bc → Bsπ decay is studied with the perturbative QCD approach. Three types of wave functions for Bs meson are considered. The transition form factor F0Bc → Bsπ （0） and the branching ratio IBr（Bc → Bsπ） are sensitive to the model of the Bs meson wave functions. With appropriate inputs, our estimate on 23r（Bc → Bsπ） is comparable with the recent LHCb measurement. A clear signal of Bc → Bsπ decay should be easily observed at the Large Hadron Collider.